Construction of Image Processing Tools Detection of Shooting Results of Female Athletes In Basketball - Ardiyansi, Yuski; Berliana, Berliana; Abduljabar, Bambang (Department of Physical Education, Sport, Health and Recreation, 2023)
Research departs from the problem of the lack of shooting tools in basketball sports in Indonesia. The purpose of this research is to contract image processing tools that are valid, reliable, and the level of norms in the throwing position is 00 (right and left), 450 (right and left), 900 (free throw). The method used in this research is using Reaserch and Development (R&D). The population in the whole women's basketball research UPI amounted to 14 athletes. Sampling uses a total sampling, with all the women's basketball athletes as much as 14 people. The results of the study resulted in the validity, reliability and level of norms, with the validity value at the position 900 of 0.867 validity being said to have high validity. Reliability value of 0.785 is moderate/sufficient. The norm Level at the overall shooting degree is A = very good, B = well, C = good enough, D = less good, and E = very less. The author can take the conclusion that construction of the image processing tool shooting tools can be used to exercise accuracy of the shooting of basketball sports, so that the results of data generated on the application can be utilized by the trainer for the placement of athletes when making an assault pattern at the time of the game